PERAN KEPALA SEKOLAH PENGGERAK TERHADAP LINGKUNGAN KERJA DI SEKOLAH DASAR - Dewi, Santi Kurnia; Mardhatillah, Mardhatillah; Suciptaningsih, Oktaviani Adhi (STKIP Persada Khatulistiwa Sintang, 2025)
A nation can be considered advanced if it has competent human resources in their respective fields. To achieve this, quality education is required. The school principal, teachers, and all related parties play a vital role in realizing education that can adapt to changes. This study aims to analyze the role of the driving school principal in creating a conducive, productive, and innovative work environment at UPT Satuan Pendidikan SDN Sapulante Pasrepan. The research method used is quantitative descriptive with data collection techniques including observation, interviews, and questionnaires. The data obtained were analyzed using descriptive statistical techniques to identify patterns and trends from the quantitative data, as well as thematic analysis for the qualitative data obtained from interviews and observations. The results show that the driving school principal plays a role as a visionary leader, motivator, manager, and role model. As a result, this has led to an increase in collaboration among teachers and educational staff, a more harmonious work atmosphere, and higher work motivation. However, the study also identifies some challenges and obstacles, such as limitations in facilities and infrastructure, differences in the competencies of school members, and resistance to change. This study concludes that the driving school principal plays a significant role in creating a conducive work environment, which ultimately supports the improvement of educational quality in the school.